2020
DOI: 10.3390/s20154348
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Older Adults’ Health Self-Management through Self-Report and Visualization—A Systematic Literature Review

Abstract: Aging is associated with a progressive decline in health, resulting in increased medical care and costs. Mobile technology may facilitate health self-management, thus increasing the quality of care and reducing costs. Although the development of technology offers opportunities in monitoring the health of older adults, it is not clear whether these technologies allow older adults to manage their health data themselves. This paper presents a review of the literature on mobile health technologies for older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…Such data are of particular importance to determine the extent to which older adults are able to cope with the use of such devices that support an active lifestyle by increasing physical exercise, decreasing social isolation, supporting social communication, and increasing participation in meaningful occupations [ 10 , 11 ]. Usage of these devices may enhance the cognitive and physical performance of community-dwelling older adults and provide monitoring technologies in order to increase their independence, autonomy, quality of life, security [ 12 , 13 , 14 ] and improve their medical management [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such data are of particular importance to determine the extent to which older adults are able to cope with the use of such devices that support an active lifestyle by increasing physical exercise, decreasing social isolation, supporting social communication, and increasing participation in meaningful occupations [ 10 , 11 ]. Usage of these devices may enhance the cognitive and physical performance of community-dwelling older adults and provide monitoring technologies in order to increase their independence, autonomy, quality of life, security [ 12 , 13 , 14 ] and improve their medical management [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to encourage self-care via digital means in the elderly, the user interface needs to be simple, easy to use, and provide consequential interaction and feedback [ 51 ]. Devices that allow patients to follow written instruction and modify care based on biological information need to be efficient and user-friendly.…”
Section: Advancing Self-care Through Technologymentioning
confidence: 99%
“…Another paper evaluated the usability problems of older adults using mHealth apps; they identifed that the most severe problems were related to navigation through the app, which was afected by slower cognitive performance, technology anxiety, learning time, and execution speed [105]. A systematic review of the literature on mobile health technologies for older adults found that only 23.5% of studies evaluated visualization features, such as clarity of information organization, ease of understanding and interpretation of displayed images, or the "look and feel" of the visualizations [10].…”
Section: Health Data Representation For Older Adultsmentioning
confidence: 99%